Green approach and strategies for wastewater treatment using bioelectrochemical systems: A critical review of fundamental concepts, applications, mechanism, and future trends. (December 2021) - Al-Sahari, Mohammed; Al-Gheethi, Adel; Radin Mohamed, Radin Maya Saphira; Noman, Efaq; Naushad, M.; Rizuan, Mohd Baharudin; Vo, Dai-Viet N.; Ismail, Norli
Abstract: Millions of litters of multifarious wastewater are directly disposed into the environment annually to reduce the processing costs leading to eutrophication and destroying the clean water sources. The bioelectrochemical systems (BESs) have recently received significant attention from researchers due to their ability to convert waste into energy and their high efficiency of wastewater treatment. However, most of the performed researches of the BESs have focused on energy generation, which created a literature gap on the utilization of BESs for wastewater treatment. The review highlights this gap from various aspects, including the BESs trends, fundamentals, applications, and mechanisms. A different review approach has followed in the present work using a bibliometric review (BR) which defined the literature gap of BESs publications in the degradation process section and linked the systematic review (SR) with it to prove and review the finding systematically. The degradation mechanisms of the BESs have been illustrated comprehensively in the current work, and various suggestions have been provided for supporting future studies and cooperation. Graphical abstract: Image 1 Highlights: Wastewater treatment using bioelectrochemical systems (BESs) is defined as a literature gap. BESs researches trends determined the shortage of publications in some of the BESs types. An innovative image is provided to illustrate the degradation mechanism of organic compounds by bacterial cells.